2010
DOI: 10.1519/jsc.0b013e3181dba178
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Strength and Endurance Training on Treadmill Load Carrying Walking Performance in Aging Men

Abstract: The present study examined the effects of twice weekly total body strength training (ST), endurance cycling (ET), and combined ST and ET (2+2 times a week) (SET) training on the load carrying walking test performance on the treadmill (TM) and changes in neuromuscular and endurance performance during a 21-week training period in aging men. Forty healthy men (54.8+/-8.0 years) were divided into 3 training groups (ET n=9, ST n=11, SET n=11) and a control group (C, n=9). Peak oxygen uptake (VO2peak), heart rate, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 35 publications
6
37
0
5
Order By: Relevance
“…Thus, maximal muscle strength gains may be mediated largely by adaptations in the nervous system during the first months of RT. Indeed, this is supported by previous findings in the part of the present subjects showing significant RT-induced increases in the m.vastus lateralis and/or medialis electromyography activity (Häkkinen et al 1998;Häkkinen et al 2000a, b;Häkkinen et al 2001a, b;Holviala et al 2010;Karavirta et al 2011a;Mikkola et al 2012;Holviala et al 2012;Walker et al 2014). Interestingly, some of the present subjects respond poorly in hypertrophy (i.e., ranked to lowest quintile in muscle size changes in Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, maximal muscle strength gains may be mediated largely by adaptations in the nervous system during the first months of RT. Indeed, this is supported by previous findings in the part of the present subjects showing significant RT-induced increases in the m.vastus lateralis and/or medialis electromyography activity (Häkkinen et al 1998;Häkkinen et al 2000a, b;Häkkinen et al 2001a, b;Holviala et al 2010;Karavirta et al 2011a;Mikkola et al 2012;Holviala et al 2012;Walker et al 2014). Interestingly, some of the present subjects respond poorly in hypertrophy (i.e., ranked to lowest quintile in muscle size changes in Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The majority of the studies reported that concurrent training induced similar strength adaptations using two sessions per week of each modality on separate days (i.e., strength and endurance) when compared with strength training alone (Holviala et al 2010;Sillampää et al 2008;Karavirta et al 2011). However, concurrent training sessions three times per week can result in an interference effect in the elderly, because greater strength gains are observed in the strength training group when compared with the concurrent training group when this weekly frequency is performed (Cadore et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Twelve original research studies that investigated the effects of concurrent training in the elderly were included, and their results were described. From these studies, 10 compared the effects of concurrent training with strength training and endurance training that were performed alone (Wood et al 2001;Izquierdo et al 2004;Sillampää et al 2008Sillampää et al , 2009aCadore et al 2010Cadore et al , 2011aHolviala et al 2010Holviala et al , 2011Karavirta et al 2009Karavirta et al , 2011, and two studies compared different types of concurrent training (Cadore et al 2012a, b).…”
Section: Inclusion Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies were primarily focused on effects of the Pilates exercise on body composition, trunk flexibility and posture stability (Donahoe-Fillmore et al, 2007;Otto et al, 2004;Wells et al, 2012). A combination of strength and endurance training in elderly populations has been postulated as the most effective strategy for improving neuromuscular and cardiorespiratory functions, to maintain functional capacity, and to promote health (Cadore et al, 2011;Holviala et al, 2010). The workplace has become a key target for health promotion programmes aimed at increasing physical activity and preventing chronic disease (WHO, 2002a,b;WHO & World Economic Forum, 2008).…”
Section: Introductionmentioning
confidence: 99%